3‐Octanoylthio‐1‐propyltriethoxysilane functionalized silica/rubber composites for application in tire: Structure, performance and synergism. Issue 10 (6th July 2022) - Das, Saikat; Pal, Kaushik; Chattopadhyay, Santanu; Bhowmick, Anil K.
Abstract: Increasing the polymer‐filler interaction is a challenge to develop high performance rubber composites. In this study, a new blocked mercaptosilane (3‐Octanoylthio‐1‐propyltriethoxysilane) was used to increase the rubber‐silica interaction by modifying highly dispersible silica and fumed silica surface with this silane. A two‐step process was used for the modification. Successful hydrolysis and condensation reaction was proved by Fourier‐transform infrared spectroscopy. Grafting density and grafting percentage were determined using thermogravimetric analysis. The modified silica/rubber composites were compared with the compositions where silane was separately added during mixing. Dynamic modulus versus strain signatures demonstrated strong polymer‐filler interaction after functionalization of the silica surface. The composites containing modified silica demonstrated improved mechanical properties and abrasion resistance over the unmodified one, which were correlated with the dispersion index. Dynamic mechanical analysis showed 28% improvement of rolling resistance and 67% improvement of ice traction after modification. Amount of silane modified silica also varied in total filler loading for precipitated silica/rubber composites. Silica‐rubber composites, where hybrid silica structure (75/25 modified and pristine silica ratio) was used, displayed interesting property to fulfill the requirement of green tire composites. Such a finding can be extended to developing tires for energy efficient vehicles.